الآليات الدولية في مكافحة غسيل الأموال - Khalaf, Kamal; Jalal, Mahmod; Almobayed, Shade (Latakia University Journal - Economic and Legal Sciences Series, 2019)
الآليات الدولية في مكافحة غسيل الأموال كمال خلف محمود جلال شادي المبيض تسعى جميع الدول إلى جذب رؤوس الأموال الأجنبية, وتشجيع الاستثمارات على أراضيها في ظل الانفتاح الاقتصادي الدولي, ومن خلال التقدم التقني والتكنولوجي, إلى أن أصبح من السهل انتقال رؤوس الأموال بين الدول, والذي حمل في طياته إخفاء للمصدر غير المشروع لهذه الأموال وهذا ما يعرف بغسيل الأموال. ولا تعد ظاهرة غسيل الأموال ظاهرة جديدة, بل هي قديمة قدم الحاجة لإخفاء الثروات المتحصلة من أنشطة غير مشروعة, حيث يعتبر غسيل الأموال, جريمة لاحقة لأنشطة جرمية حققت عوائد مالية غير مشروعة, فكان لزاما إضفاء المشروعية على العائدات الجرمية أو ما يسمى الأموال القذرة ليتاح استخدامها فيما بعد بيسر وسهولة, كتجارة المخدرات وتهريب الأسلحة والاتجار بالبشر, ومن هذا المنطلق يمكن القول أن غسيل الأموال من الجرائم الاقتصادية الخطيرة التي تمس الاستقرار المالي والاقتصادي للدول, ابتداء من التحصيل لهذه الأموال ثم توظيفها في البنوك والاستثمار في المشاريع. ولغسيل الأموال آثار اقتصادية و اجتماعية مدمرة من أهمها: زيادة معدل الإجرام و انخفاض معدل الدخل القومي و تدهور قيمة العملة الوطنية, ويعزى انتشار هذه الظاهرة لعدد من الأسباب الموضوعية أو الإجرائية ومنها ما يأتي من قصور الجانب التشريعي أو غياب التعاون بين المعنيين, ولمواجهة هذه الظاهرة وانعكاساتها السلبية على الاقتصاد الوطني سارعت الدول إلى بذل جهود كبيرة لمكافحة غسيل الأموال على الصعيد الداخلي وعلى الصعيد الدولي من خلال إصدار جملة من القوانين الداخلية وإبرام اتفاقيات دولية في هذا المجال كاتفاقية فيينا لعام 1988, لمكافحة التجارة غير المشروعة بالمخدرات والمؤثرات العقلية, واتفاقية المجلس الأوروبي لعام 1990. All countries seek to attract foreign capital and to encourage investments in their territories in the light of international economic openness and through technical and technological progress until it is easy to transfer capital between countries, which has concealed the illegal source of these funds, Money. Money-laundering is not a new phenomenon, it is as old as the need to conceal the wealth obtained from illicit activities. Money-laundering is a crime that follows criminal activities that have generated illegal financial returns. The proceeds of crime or so-called dirty money have to be legitimized It can be said that money laundering is one of the most serious economic crimes affecting the financial and economic stability of countries, from the collection of these funds to the use of banks and investment in projectsl. The laundering of money has devastating economic and social effects, the most important of which are: the increase in the rate of criminality, the decline in the rate of national income and the deterioration of the value of the national currency. The spread of this phenomenon is attributed to a number of objective or procedural reasons, including the lack of legislative aspect or lack of cooperation between the concerned parties, And their negative impact on the national economy, States have made great efforts to combat money laundering at the domestic and international levels through the promulgation of a number of domestic laws and the conclusion of international conventions in this area such as the Vienna Convention of 1988 to Combat Illegal Trade Narcotic Drugs and Psychotropic Substances, and the 1990 European Council Convention.